(untitled) (Clinics, 2015)
OBJECTIVES: Carotid artery stenting is an emerging revascularization alternative to carotid endarterectomy. However, guidelines have recommended carotid artery stenting only if the rate of periprocedural stroke or death is < 6% among symptomatic patients and < 3% among asymptomatic patients. The aim of this study is to evaluate and compare clinical outcomes of symptomatic and asymptomatic patients who had undergone carotid artery stenting as a first-intention treatment. METHOD: A retrospective analysis of patients who underwent carotid artery stenting by our interventional neuroradiology team was conducted. Patients were divided into two groups: symptomatic and asymptomatic patients. The primary endpoints were ipsilateral ischemic stroke, ipsilateral parenchymal hemorrhage and major adverse cardiac and cerebrovascular events at 30 days. The secondary endpoints included ipsilateral ischemic stroke, ipsilateral parenchymal hemorrhage, ipsilateral transient ischemic attack and major adverse cardiac and cerebrovascular events between the 1- and 12-month follow-ups. RESULTS: A total of 200 consecutive patients were evaluated. The primary endpoints obtained in the symptomatic vs. asymptomatic groups were ipsilateral stroke (2.4% vs. 2.7%, p = 1.00), ipsilateral parenchymal hemorrhage (0.8% vs. 0.0%, p = 1.00) and major adverse cardiac and cerebrovascular events (4.7% vs. 2.7%, p = 0.71). The secondary endpoints obtained in the symptomatic vs. asymptomatic groups were ipsilateral ischemic stroke (0.0% vs. 0.0%), ipsilateral parenchymal hemorrhage (0.0% vs. 0.0%), ipsilateral TIA (0.0% vs. 0.0%, p = 1.00) and major adverse cardiac and cerebrovascular events (11.2% vs. 4.1%, p = 0.11). CONCLUSIONS: In this retrospective study, carotid artery stenting was similarly safe and effective when performed as a first-intention treatment in both symptomatic and asymptomatic patients. The study results comply with the safety requirements from current recommendations to perform carotid artery stenting as an alternative treatment to carotid endarterectomy.